Comparison of Toxoplasma gondii Cysts Predilection in the Heart and Diaphragm of Pig in Bali - I Wayan Wirata (Jurnal Sain Veteriner, 2014)
A study was conducted on Toxoplasma gondii in the heart and diaphragm of pigs in Bali. The study was aimed to compare the predilection of Toxoplasma gondii cysts in the hearts and diaphragms of pigs and compared to the number of T. gondii cysts per gr from the hearts and diaphragm sof infected pigs. Pigs were examined as many as 171. Each organ was examined by digestion method in order to identify the presence of T. gondii cysts in these organs. The parameters measured were the percentages and numbers of T. gondii cysts which werefound in each organs. The results showed that 9 of pigs were infected with T. gondii (5,26%) which in the hearts and diaphragms were 4.09% and 1.17%, respectively. The average number of T. gondii cysts per gr of the heart and diaphragm were 30.86 ± 21.38 and 24, respectively.